Bioactive phosphate glass-based fiber with green persistent luminescence - Lemiere A; Szczodra A; Vuori S; Bondzior B; Hawkins TW; Ballato J; Lastusaari M; Massera J; Petit L (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
The first biophotonic composite fiber with green persistent luminescence is reported. The composites were drawn from preforms prepared by remelting a bioactive glass with commercial persistent luminescent microparticles (SrAl2O4:Eu2+,Dy3+). The duration of the remelt step should be as short as possible to limit the decomposition of the micro-phosphors during glass preparation, as evidenced using electron microscopy coupled with elemental analysis. The presence of the phosphors in the glass inhibits the drawing of fibers with diameter below about 400 µm. Although the drawing process induces some changes in the Eu2+ ions’ local structure in the phosphors, the fibers still exhibit green afterglow. Despite the presence of the phosphors, the fiber still maintains its bioactive response, as characterized by the release of ions from the glass to the environment and the successive precipitation of a reactive layer within a dicalcium phosphate dehydrate composition.